(untitled) (Semiárida, 2017)
Changes in land use produce significant modifications of ecosystem structure and functioning. Associated with decreasing contents of organic matter (MO) they would produce changes in soil macroporosity that might condition a lower water use efficiency, emphasizing processes of soil physical degradation. The objective was to evaluate the effects of different uses on soil properties related to compaction. The study was conducted at experimental sites of the National Water Program of INTA, over 52 soils under two contrasting managements: virgin or pasture (V: 26 soils) and agriculture (A: 26 soils). They were grouped by soil moisture regime: ustic (Us: 36 soils) and udic (Ud: 16 soils). Maximum apparent density (DAm) decreased with increasing clay + silt contents (A + L) (A: R2= 0.60, p= 0.0001 V: R2= 0.44, p= 0.0016). Also significant was the influence of MO on bulk density (DA) and the susceptibility to compaction (SC) in soils of both moisture regimes. These changes could possibly explain much of the loss of infiltration, increased flooding, crusting and / or runoff from soils that under determined use have lost MO. DOI: http://dx.doi.org/10.19137/semiarida.2016(02).19-26